Durability and mechanical performance of differently treated glulam beams during two years of outdoor exposure : Trajnost i mehanička svojstva različito obrađenih lameliranih nosača tijekom dvije godine izlaganja u eksterijeru - Kržišnik, Davor (Array, 2020)
The performance of the composites is influenced by the service life of input raw wood material and used adhesives. The aim of the study was to assess the durability and mechanical performance of glulam beams treated in a different way (thermally modified and/or treated with copper-based wood preservative) and exposed in an outdoor application. Glulam beams (83 mm × 68 mm × 1100 mm), made of three layers of Norway spruce (Picea abies) with PUR adhesives used have been exposed in use class 3.2 in a horizontal position since 4th November 2016. Part of the specimens was equipped with MC sensors. Every year, the degradation was evaluated visually. The dynamic modulus of elasticity was determined by longitudinal vibration, and the static modulus of elasticity using a 4-point bending test. On the smaller specimens, cut from glulams, compressive strength, delamination, and shear strength of adhesive bonds were determined. After two years of exposure, the results indicate that the performance of glulams is determined by the wood modification and applied wood preservative.